1.2 e⁻¹¹
Because you need a number between 1 and 10 for scientific notation. So you move the decimal over 11 places. Since you move it to the right, it becomes a negative exponent.
Pls provide the complete question.
Answer:
(2x - 3) ^2
Step-by-step explanation:
Factor using the perfect square rule.
Answer:
x = 11/3 = 3 2/3
y = 13/3 = 4 1/3
Step-by-step explanation:
Here, we want to solve the system of equations simultaneously
x + y = 8
2x -3 = y
From the second equation, we have an equation for y
we can simply proceed to substitute this into the first equation
x + 2x - 3 = 8
3x - 3 = 8
3x = 8 + 3
3x = 11
x = 11/3
Recall;
y = 2x - 3
y = 2(11/3) - 3
y = 22/3 - 3
y = (22-3(3))/3
y = (22-9)/3 = 13/3